Mathematical critical thinking ability in terms of mathematical anxiety in Smart Card assisted Brain-Based Learning model - Rohmah, Naila Zulfatur; Mashuri, Mashuri (Unnes Journal of Mathematics Education, 2021)
This study aims to analyze the effectiveness of the Smart card-assisted Brain-Based Learning model against mathematical critical thinking skills, to analyze whether the smart card-assisted Brain-Based Learning model is more effective than the Treffinger model for mathematical critical thinking skills, and to describe students' mathematical critical thinking skills in terms of mathematical anxiety. This research applied quantitative method followed by a description. The population in this research were students of the seventh-grades on three of Junior High School in Ungaran in the academic year 2019/2020. This research applied the cluster random sampling technique as the technique for collecting the data. The subject of the research was selected from the experimental class. The researcher was used purposive sampling technique to select the subject of this research. The data was collected by using the test method, the questionnaire method, and the interview method. The quantitative data analysis used classical completeness test, mean difference test, and proportion difference test. The result of this study indicate that smart card-assisted Brain-Based Learning model is effective for mathematical critical thinking skills, but smart card-assisted Brain-Based Learning model is no more effective than Treffinger on mathematical critical thinking skills. In addition, the description of mathematical critical thinking skills in terms of mathematical anxiety is obtained that: (1) subjects with low mathematical anxiety are able to achieve the indicator (A) clarification well, indicator (B) assessments well, indicator (C) concludes well, and indicator (D) strategy well; (2) subjects with moderate mathematical anxiety are able to achieve indicator (A) well, indicator (B) well, indicator (C) quite well, and indicator (D) quite well; (3) subjects with high mathematical anxiety are able to achieve indicator (A) well, indicator (B) is quite good, indicator (D) is quite good.